Isocoumarin, thiaisocoumarin and phosphaisocoumarin : natural occurrences, synthetic approaches and pharmaceutical applications /: natural occurrences, synthetic approaches and pharmaceutical applications. (2018) - Pal, Sarbani; Pal, Manojit
No abstract available